Demonstration and Counseling on the Preparation of Moringa Leaf Porridge for Stunting Prevention and Growth - ImamAlAyyubi, Ibnu; Prayetno, Eko; Nurhikmah, Nurhikmah; Noerzanah, Firda; Musaldin, LaOde (Kusuma: Jurnal Pengabdian kepada Masyarakat, 2025)
The counseling and demonstration activities on the preparation of Moringa leaf porridge successfully enhanced the knowledge of the community, particularly mothers in Wawobeau Village, about the importance of nutrition in preventing stunting in children. Through the education provided, participants understood the nutritional benefits of Moringa leaves and how they can be processed into nutritious food. The participants’ enthusiasm during the event demonstrated a high awareness of the importance of proper nutrition for children. This activity is expected to encourage the community to utilize local resources, such as Moringa leaves, to improve children's health and growth, and reduce the risk of stunting in the area. It also highlighted the importance of collaboration between the posyandu cadres and the community in raising awareness about child nutrition and health. Although the activity was successful, there were some challenges in its implementation and preparation, including difficulties faced by some respondents in identifying basic knowledge related to the material presented. This indicates the need for further evaluation of how information is conveyed to ensure better understanding by all participants. Additionally, the low attendance was partly due to scheduling conflicts and other commitments, preventing some invited members of the community from attending. For future research, it is recommended to provide the material periodically and in an easily understandable format, as well as to invite a larger number of participants.